Dampak Shadaqah Pada Keberlangsungan Usaha (Studi Kasus: Testimoni 4 Pengusaha Muslim di Surabaya) - Sami, Abdus; Nafik HR, Muhammad (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aims to identify and explain the impact on business continuity shadaqah Muslim businessmen in Surabaya. It is the basis for explaining the impact of interview questions Sadaqah on business continuity in terms of operating income, number of employees, provide the best performance, business development, business growth, business resilience.This study used a qualitative approach with a case study strategy. Data was collected through interviews and direct observation to study the object. The analysis technique used in this study is a qualitative analysis of explanatory approach to explain the results of interviews and direct observation.The results of this study indicate that there is a Sadaqah impact on business continuity Muslim businessmen in Surabaya. The more routine Muslim businessmen in doing charity it will affect the performance of the business that will have an impact on business continuity achieved.